2021
DOI: 10.4236/gep.2021.98002
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Semi-Distributed SWAT (Soil and Water Assessment Tool) Model Capacity in the Lobo Watershed at Nibéhibé (Center-West of Côte D’Ivoire)

Abstract: The Lobo watershed is an agricultural area where the use of fertilizers by farmers is intensive, causing eutrophication problems that deteriorate the quality of drinking water distributed to the population. Since the phenomenon of eutrophication is directly linked to runoff, it is essential to model the flow in order to better control the transfer of nutrients responsible for eutrophication. It is within this framework that this study was conducted. The objective of this study is to assess the ability of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…The QSWAT is a hydrological model that can simulate physical basins by distributing the parameters according to the physical conditions of the actual area. It is also able to predict the effects of climate change and land use on runoff, sediment, and agricultural chemicals [36][37][38][39][40][41]. In addition, its calculation process is highly reliable and is widely used not only in Thailand, but also around the world [42].…”
Section: Qswat Modelmentioning
confidence: 99%
“…The QSWAT is a hydrological model that can simulate physical basins by distributing the parameters according to the physical conditions of the actual area. It is also able to predict the effects of climate change and land use on runoff, sediment, and agricultural chemicals [36][37][38][39][40][41]. In addition, its calculation process is highly reliable and is widely used not only in Thailand, but also around the world [42].…”
Section: Qswat Modelmentioning
confidence: 99%
“…The Lobo reservoir is used by the Cote d'Ivoire Water Distribution Company (SODECI) to supply drinking water to the Daloa town populations and its surrounding areas as well as to meet the water needs of agropastoral activities. The work carried out by Koua et al [8], Soro et al [9], N'goran et al [10] showed a spatial distribution of nutrients from mineral fertilizers applied to plants. This distribution predisposes ivorian reservoirs, particularly the Lobo reservoir to an enrichment of nutrient elements responsible for the observed eutrophication phenomenon in that reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…MDPI and/or the editor(s) disclaim responsibility for any injury to people or property resulting from any ideas, methods, instructions, or products referred to in the content. 2 eutrophication problems [4]. The case of the Lobo reservoir highlighted by Maïga et al [5] is representative.…”
Section: Introductionmentioning
confidence: 99%